Protective effect of higher free thyroxine levels within the reference range on biliary tract cancer risk: a multivariable mendelian randomization and mediation analysis - Chen, Yuxian; Dong, Hao; Qu, Baozhen; Ma, Xuezhen; Lu, LinLin (Frontiers in Endocrinology, 2024)
Background: Hepatobiliary cancer (HBC), including hepatocellular carcinoma (HCC) and biliary tract cancer (BTC), are currently one of the malignant tumors that mainly cause human death. Many HBC are diagnosed in the late stage, which increases the disease burden, indicating that effective prevention strategies and identification of risk factors are urgent. Many studies have reported the role of thyroid hormones on HBC. Our research aims to assess the causal effects and investigate the mediation effects between thyroid function and HBC. Methods: Utilizing the Mendelian randomization (MR) approach, the study employs single nucleotide polymorphisms (SNPs) as instrumental variables (IVs) to explore causal links between thyroid function [free thyroxine (FT4), thyroid stimulating hormone (TSH), hyperthyroidism and hypothyroidism] and HBC. Data were sourced from the ThyroidOmic consortium and FinnGen consortium. The analysis included univariable and multivariable MR analysis, followed by mediation analysis. Results: The study found a significant causal association between high FT4 levels and the reduced risk of BTC, but not HCC. However, TSH, hyperthyroidism and hypothyroidism had no causal associations with the risk of HBC. Notably, we also demonstrated that only higher FT4 levels with the reference range (FT4-RR) could reduce the risk of BTC because this protective effect no longer existed under the conditions of hyperthyroidism or hypothyroidism. Finally, we found that the protective effect of FT4-RR on BTC was mediated partially by decreasing the risk of metabolic syndrome (MetS) and reducing the waist circumference (WC). Conclusion: The findings suggest that higher FT4-RR may have a protective effect against BTC, which is partially mediated by decreased risk of MetS and a reduction in WC. This study highlights the potential role of FT4 in the pathogenesis of BTC and underscores that MetS and WC may play mediation effects as two mediators in this process.